Towards the Clinical Evaluation of the Luteal Phase in Fertile Women: A Preliminary Study of Normative Urinary Hormone Profiles - Alliende, María Elena; Arraztoa, José Antonio; Guajardo, Ulises; Mellado, Fernando (Frontiers in Public Health, 2018)
Abstract Objective: To describe and evaluate urinary hormone profiles in the luteal phase Setting and Patients: 25 healthy fertile women, with regular ovulatory pattern cycles as assessed by temperature and cervical mucus, at a university based center. Methods: Daily urinary hormonal assessment of luteinizing hormone, estrone glucuronide and pregnanediol glucuronide. This was done during 3 or more cycles, with 78 completed cycles. Samples were analyzed by both crude levels and levels adjusted for the hormone excretion rate. Correlation between measured parameters (LH surge, vulvar mucus) was assessed with regard to their ability to detect presumed ovulation. Results: An upper, middle and lower tercile range for the main urinary reproductive hormones was determined and a classification system of zones proposed, considering profiles over or under the 10th percentile. Adjustment for the urine excretion rate proved useful for interpreting individual samples; this was less necessary with multiple samples over time where trends could be determined. This serial evaluation, in at least two cycles, lowered the possibility of finding an isolated luteal phase defect and helped identify the recurrence of such. Vulvar mucus findings performed well in determining the timing of ovulation. Despite the proven fertility of the study population, lower luteal phase hormones were detected in both an isolated and, in some situations, recurrent manner. Conclusion: A feasible method is proposed to accurately, thoroughly and reproducibly study the luteal phase in order to evaluate and treat identified abnormalities in a properly timed, restorative manner. This preliminary study provides the basis for future research, correlating urinary hormones with clinical findings, particularly those of luteal phase defects.